PEMBELAJARAN MATERI LETAK ASTRONOMIS PADA SISWA KELAS V DENGAN MENGGUNAKAN METODE MIND MAPPING BERBANTUAN MEDIA GLOBE DAN ATLAS. - Senny Nadya Permatasari; Uus Kuswendi (IKIP Siliwangi, 2021)
This research has three objectives, (1) Knowing the scenario and implementation of learning material in astronomical location using the Mind Mapping method approach assisted by Globe and Atlas media; (2) Knowing the response of teachers and students to learning; (3) Finding the difficulties experienced by students in completing the assigned task. This approach uses a qualitative descriptive approach. Data collection techniques using observation, interviews, documentation, and questionnaires. Data research procedures, namely, (1) preparation; (2) Planning; (3) Observation / data collection; (4) Implementation; (5) Data analysis. The data were processed using Microsoft Excel to calculate the questionnaire data. The results showed the implementation of learning took place as planned in the scenario. Teachers and students give good responses to learning. The difficulties the students found were (a) the students ran out of time (b) the students had difficulty finding keys (c) some students did not like drawing.